5g+7g and g(5+7) g=6

Asked By Ryan On 03/21/2017 02:12

Answers

5g + 7g = 12g g ( 5 + 7 ) = 12 g and if g = 6, then 12 g = 12 (6) = 72.
Answered On 03/21/2017 04:31


If I'm reading your problems correctly, the solution lies in substitution. Simply plug in 6 in place of the variable g in both problems. Whenever you substitute a number in place of a variable, always place your number inside parentheses. This way there is no confusion as to when you need to multiply. Problem #1 5g + 7g when g = 6 5(6) + 7(6) = 30 + 42 = 72 Problem #2 g(5 + 7) g = 6 (6)(5 + 7) Simplify inside your parentheses = (6)(12) Multiply = 72
Answered On 03/21/2017 13:43